HOW ACCOUNTING STUDENTS PERCEIVE THE CONTRIBUTION OF ACCOUNTANTS FOR THE ADOPTION OF SUSTAINABILITY AND GREEN IT PRACTICES IN ORGANIZATIONS - da Silva, Raphael Junger; Gomes, Mônica Zaidan; Sancovschi, Moacir (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
This study evaluated the importance of sustainability and Information Technology/Information System (IT/IS) disciplines in building up perceptions of undergraduate and graduate accounting students’ in the Metropolitan Region of Rio de Janeiro with respect to sustainability in IT/IS. The results confirm the findings of the literature that many accounting students reach the end of the course without any contact with theses disciplines and that, in the respondents’ perception, the most important contribution of accountants to sustainability in IT/IS is controlling and evaluating the performance of physical and financial IT indicators. On the other hand, one of the least important contributions was reporting IT environmental performance to external users. Also, the number of subjects covered in IT/IS and sustainability throughout academic life of the students has the power to influence the respondents’ perception of the importance they attribute to the subjects.